Podstawy datowania grodów kultury łużyckiej na ziemiach polskich - Góralczyk, Agnieszka (Folia Praehistorica Posnaniensia, 2024)
The article contains a detailed analysis of 116 verified Lusatian culture stronghold sites from Polish lands, more or less archaeologically surveyed and with published research results. 64 of these have been identified as the remains of defensive settlements, and on 52 sites traces of later early medieval fortified settlement have also been discovered. These were investigated by surface, probing and excavation (in the case of 8 fortified settlements, the method of archaeological investigation used was not specified). The chronology of most of the sites has not been determined using all known dating methods, but mostly on the basis of pottery analysis. The article discusses the state of research from the 2nd half of the 19th century to the present day.